Optimalisasi Media Sort & Match Board untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar: Penelitian Tindakan Kelas - Aziz, Abdul; Yayuk, Erna; Astutik, Sri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to enhance the motivation and learning outcomes of 4th-grade students at SDN Ngaglik 01 Kota Batu through the implementation of the Sort & Match Board learning media. This medium integrates physical and cognitive activities to actively involve students in the learning process, thereby fostering academic improvement.Method – The research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, which includes the stages of planning, implementation, observation, and reflection. The study was conducted from November 14 to December 13, 2024, involving 23 fourth-grade students. Data was collected through observation, interviews, questionnaires, documentation, and analysis of student learning outcomes. Findings – The results revealed a significant improvement in both student motivation and academic performance. The proportion of motivated students increased from 21.7% in Cycle I to 100% in Cycle II, while the average test score rose from 60.43 to 85.57. A paired sample t-test confirmed the statistical significance of this improvement (p < 0.05). Enhancements in the visual design and instructional clarity of the media were identified as contributing factors to increased student engagement. Research Implications – The findings suggest that interactive learning media can effectively boost student motivation and academic outcomes. Nevertheless, the study's generalizability is limited by its small sample size and specific context. Future research is recommended to investigate the application of the Sort & Match Board across various subjects and educational levels.